2008
DOI: 10.1007/s00134-008-1314-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound-guided pigtail catheter for drainage of pleural effusions in the ICU

Abstract: The ultrasound-guided pigtail catheter inserted by intensivists is a well-tolerated and effective method of draining all kinds of pleural effusions in critically ill patients. We suggest that pigtail catheter drainage be considered as the initial treatment of choice in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 20 publications
4
40
2
6
Order By: Relevance
“…[45]. Conversely, the same research group found in another study that these massive transudative pleural effusions were also associated with the highest overall complication rates (6 of 33, or 18%) [36].…”
Section: Complications Of Thoracentesismentioning
confidence: 92%
See 1 more Smart Citation
“…[45]. Conversely, the same research group found in another study that these massive transudative pleural effusions were also associated with the highest overall complication rates (6 of 33, or 18%) [36].…”
Section: Complications Of Thoracentesismentioning
confidence: 92%
“…In contrast, the pneumothorax rate associated with ultrasound-guided thoracenteses was lower, ranging from 0 to 9.1%. The rates of subsequent chest tube insertion for pneumothoraces ranged from 2.2-7% in those procedures without ultrasound guidance and 0-3.7% in procedures performed with ultrasound guidance [6,13,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Overall Incidence Of Pneumothorax and Impact Of Ultrasoundmentioning
confidence: 99%
“…15 Similarly, Roberts et al, studying the efficacy of both techniques in pediatric thoracotomy, found that the use of pigtail catheters was more efficacious in draining serous effusion. 16 Chest tube drainage was superior in cases of hemothorax, chylous pleural effusion, and empyema.…”
Section: Pigtail Catheter Versus Chest Tube Drainagementioning
confidence: 97%
“…Light et al, Roberts et al, and Liang et al reported higher efficacy of chest tube in comparison to pigtail catheter for drainage of empyema. [15][16][17] Therefore, it is recommended that chest tubes are to be use at least initially for drainage of empyema, and pigtail catheter can be used after. However, some authors reported that there was no statistically significant difference between the initial use of pigtail catheter and chest tube drainage of pleural empyema, particularly when there was no evidence of loculations.…”
Section: Pigtail Catheter Versus Chest Tube Drainagementioning
confidence: 99%
“…Plevral efüzyon sonografik olarak anekoik, kompleks septalı-septasız ve homojen ekoik içerik-li olarak görülebilir. Light Kriterleri plevral efüzyonların transüda ve eksüda ayrımı için kullanılır [4]. Bu ayırım tanısal yaklaşımı ve hasta yönetimini etkiler.…”
Section: Plevral Efüzyon Ve Görüntüleme (Us Ve Bt)unclassified